COMPETITIVE STRUCTURE AND TECHNICAL EFFICIENCY OF BANKING INDUSTRY IN INDONESIA - Hadi Satria Ganefi; Wita Juwita Ermawati; Dedi Budiman Hakim (School of Business, Bogor Agricultural University (SB-IPB), 2020)
Competition is an important aspect in an industry that may affect business continuity. The practice of a market structure concentrated on five major banks caused differences in efficiency and can ultimately influence competition between banks. This study aims to analyze the structure of competition and the level of technical efficiency in the banking industry during 2014-2018 period. 79banks were grouped into business group according to the core capital and were analyzed based on the groups. This study used non-structural Panzar Rosse method to analyze the competition structure. Afterwards, non parametric DEA (data envelopment analysis) method was used to determine the level of efficiency. The results showed that the banking industry in Indonesia generally operates under monopolistic competition. In addition, based on efficiency performance, bank BUKU 4 has the highest performance. This is because large of banks can produce larger economies of scale. Keywords: market structure, banking, panzar rosse model, efficiency, Data Envelopment Analysis (DEA)